Strategic Health Purchasing Progress Mapping: A Spotlight on Ghana's National Health Insurance Scheme. Issue 2 (1st March 2022) - Amporfu, Eugenia; Agyei-Baffour, Peter; Edusei, Anthony; Novignon, Jacob; Arthur, Eric
ABSTRACT: Ghana is a lower-middle-income economy that has made significant efforts to improve its health system, in order to achieve universal health coverage. Ghana has adopted strategic health purchasing as an important tool for efficient utilization of resources. This paper focuses on Ghana's National Health Insurance Scheme (NHIS) analyzing its governance arrangements and purchasing functions; and providing recommendations for improvement. The study applied the Strategic Health Purchasing Progress Tracking Framework co-created by the Strategic Purchasing Africa Resource Center (SPARC) and its partners to collect data from secondary and primary sources between September 2019 and June 2020. A descriptive and narrative approach was used to synthesize information on the NHIS governance arrangements and purchasing functions based on the framework. Benchmarks were used to describe the NHIS on the continuum from passive to strategic purchasing and to identify steps to make purchasing more strategic. Strengths and weaknesses were found in governance and purchasing functions. Progress was seen in how the NHIS selects the services in the benefit package, regularly reviewing the package to respond to the health needs of the population, and in how it selectively contracts with providers, particularly private providers, to ensure that standards for quality of care are met. However, challenges remain in performance monitoring, due to claims being mostly processed manually, and provider payment, due to frequent unbundling and upcoding of services Ghana has made significant strides toward the achievement of universal health coverage, but there is room for improvement in provider payment and performance monitoring.